Relación entre engagement y desempeño laboral: revisión aplicada - Aguilar Barrera, Claudia Sofia (2023)
Work engagement or commitment plays an important role in employee's behavior because through it, organizational indicators and objectives can be achieved more effectively. The aim of this applied review is to identify the relationship between engagement and job performance through an exhaustive review of scientific literature about both theoretical constructs. A systematic search was carried out following the indications of the PRISMA guide (Bossuyt et al., 2020). The databases consulted were EBSCOhost, Scopus and Proquest. Articles that correlate commitment and work performance (n = 10) were selected for this applied review. As a result, it was obtained that there is a positive correlation between engagement and work performance. This applied review is considered a contribution to Organizational Psychology because it encourages and allows strategies to improve the working conditions of employees so that they can feel engaged and in turn perform better in the organization.